Contribution of Agricultural Infrastructure to Rural Development in the Republic of Korea. (3rd May 2016) - Im, Sang Bong; Lee, Sang‐Hyun; Lee, Jemyung; Kim, Taegon
Abstract: The aim of the study is to analyse the effects of large‐scale agricultural infrastructure investment on rural development. Accordingly, we selected the Yeongsan River Basin Comprehensive Development Project (YRBCADP) as the case project and evaluated the impacts of YRBCADP on agricultural and regional development individually. In terms of agricultural development, YRBCADP has contributed to the increase of farmland area, agricultural productivity, and farm income. The farmland of the project area was increased about 3.5 times, from 43 000 ha in 1970 to 150 000 ha in 2010, and the average rice yield per area was 3.97 t ha ‐1 in 1973. In addition, YRBCADP has affected regional development positively, such as population, regional income, and transportation accessibility. The ratio of population decrease was 25.6% in the project area but was 41.8% in the no‐project area. The local tax per capita in the project area increased from 123 to 1747 million won in the period 1991–2011. The tidal embankment in YRBCADP has shortened travel distance, thus transportation costs were also reduced. This study reviewed the various effects of YRBCARD on rural development, and these results might offer useful information for making decisions for large‐scale agricultural infrastructure investment. Copyright © 2016 John Wiley & Sons, Ltd.